Promoting physical activity with a school-based dance mat exergaming intervention: qualitative findings from a natural experiment - Duika Burges Watson; Jean Adams; Liane B. Azevedo; Catherine Haighton (BMC, 2016)
Abstract Background Physical activity is critical to improving health and well-being in children. Quantitative studies have found a decline in activity in the transition from primary to secondary education. Exergames (active video games) might increase physical activity in adolescents. In January 2011 exergame dance mat systems were introduced in to all secondary schools across two local authority districts in the UK. We performed a quasi-experimental evaluation of a natural experiment using a mixed methods design. The quantitative findings from this work have been previously published. The aim of this linked qualitative study was to explore the implementation of the dance mat scheme and offer insights into its uptake as a physical activity intervention. Methods Embedded qualitative interviews at baseline and 12 month follow-up with purposively selected physical education teachers (n = 20) and 25 focus groups with a convenience sample of pupils (n = 120) from five intervention schools were conducted. Analysis was informed by sociology of translation approach. Results At baseline, participants (both teachers and pupils) reported different expectations about the dance mats and how they could be employed. Variation in use was seen at follow-up. In some settings they were frequently used to engage hard to reach groups of pupils. Overall, the dance mats were not used routinely to increase physical activity. However there were other unanticipated benefits to pupils such as improved reaction time, co-ordination and mathematic skills. The use of dance mats was limited in routine physical education classes because of contextual issues (school/government policy) technological failures (batteries/updates) and because of expectations about how and where they could be used. Conclusions Our linked quantitative study (previously published) suggested that the dance mats were not particularly effective in increasing physical activity, but the qualitative results (reported here) show that the dance mats were not used routinely enough to show a significant effect on physical activity of the intervention. This research demonstrates the benefit of using mixed methods to evaluate complex physical activity interventions. Those planning any intervention for promoting physical activity in schools need to understand the distinction between physical activity and physical education.